THE EFFECT OF NPL AND LDR ON PROFITABILITY MEDIATED BY OPERATIONAL EFFICIENCY IN IDX BANKS - Oktaviani Oktaviani; Indra Widjaja (Graduate Program of Universitas Tarumanagara, 2025)
This study examines the effect of NPL and LDR on banking profitability, with Operational Efficiency (BOPO) as a mediating variable. Using a descriptive quantitative approach, data from eight KBMI V banks listed on the Indonesia Stock Exchange (IDX) during 2019–2023 were analyzed. A total of 40 observations were selected through purposive sampling. The analysis employed panel data regression with the Random Effect Model and the Sobel test via Eviews 13 SV. Results reveal that NPL and LDR positively affect BOPO and Return on Assets (ROA), while BOPO negatively influences ROA. BOPO significantly mediates the NPL–ROA relationship but not LDR–ROA. These findings underscore the importance of controlling NPLs, improving credit quality, and enhancing operational efficiency to support sustainable bank profitability.